2018
DOI: 10.1038/s41598-018-27643-3
|View full text |Cite
|
Sign up to set email alerts
|

The lincRNA MIRAT binds to IQGAP1 and modulates the MAPK pathway in NRAS mutant melanoma

Abstract: Despite major advances in targeted melanoma therapies, drug resistance limits their efficacy. Long noncoding RNAs (lncRNAs) are transcriptome elements that do not encode proteins but are important regulatory molecules. LncRNAs have been implicated in cancer development and response to different therapeutics and are thus potential treatment targets; however, the majority of their functions and molecular interactions remain unexplored. In this study, we identify a novel cytoplasmic intergenic lincRNA (MIRAT), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…IQGAP1 has also been reported to play important roles in regulating the microtubule network, actin cytoskeleton and cell adhesion 9 . IQGAP1 has been demonstrated to be regulated by miR-23b cluster, miR-125a-5p 25 , Long noncoding RNA (MIRAT) 26 and promote RAS-MAP kinase-driven cancer invasion 27 . In addition, a significant increase in angiogenesis by the overexpression of IQGAP1 was found in an in vivo mouse model of breast cancer 28 .…”
Section: Discussionmentioning
confidence: 99%
“…IQGAP1 has also been reported to play important roles in regulating the microtubule network, actin cytoskeleton and cell adhesion 9 . IQGAP1 has been demonstrated to be regulated by miR-23b cluster, miR-125a-5p 25 , Long noncoding RNA (MIRAT) 26 and promote RAS-MAP kinase-driven cancer invasion 27 . In addition, a significant increase in angiogenesis by the overexpression of IQGAP1 was found in an in vivo mouse model of breast cancer 28 .…”
Section: Discussionmentioning
confidence: 99%
“…MAPK Inhibitor Resistance Associated Transcript (MIRAT), a cytoplasmic intergenic lncRNA, functions by binding to the scaffold protein IQ motif containing GTPase activating protein 1 IQGAP1 [ 51 ], a protein facilitating MEK/ERK pathway signaling. MIRAT stabilizes IQGAP1 and inhibits its decay [ 91 , 92 ].…”
Section: Protein-lncrna Interactions In Melanomamentioning
confidence: 99%
“…On the other hand, the specific silencing of the MIRAT lncRNA in such resistant cells restores sensitivity to MEK inhibitors. Authors suggested that MIRAT lncRNA binds to IQGAP1—boosting MEK to ERK signaling and hyper-activation in different cancer types—and stabilizes it, thus pushing MAPK signaling [ 34 ].…”
Section: Prognostic Value Of Lncrnas In Cutaneous Melanoma and Thementioning
confidence: 99%